Addition of egbe and ethanol to enhance mes performance as chemical flooding material - Dewi Tristantini; Humala Paulus Hakim; Muhammad Fadly Zuliardy (Jurnal Teknik Kimia Indonesia, 2011)
Methyl ester sulfonate (MES) performance as chemical flooding material for EOR was investigated by adding emulsifier ethyl glycol mono butyl ether (EGBE) and ethanol. MES had interfacial tension (IFT) value as low as 10-3 dyne/cm, but its disadvantage was low solubility in brine water. Repairing this nature, MES was modified by adding nonyl phenol ethoxylate (Tergitol, as secondary surfactant), EGBE and ethanol. The mixed surfactant was tested for IFT value, solubility, and thermal influence to IFT value in various concentrations. The result indicated a significant effect of emulsifier concentration to IFT value. The longer carbon chains, the easier micelle interaction was formed. The positive effects to solubility were caused by the polarity of long chain EGBE and the increase of micro emulsion stability by ethanol. The best formulas were 1% concentration surfactant in brine water consist of MES 40%, Tergitol 20%, ethanol 40% and 0.3% of MES 40%, Tergitol 20%, EGBE 40%. These formulas also had better solubility than MES alone, since they only form one phase. Heat treatment at 62.5 oC for 1 day caused lower IFT because of increasing interaction between emulsifier and micelle. Further heating resulted in a higher IFT as the emulsifier structure collapsed, which made interactions difficult to achieve. Keywords: EOR, interfacial tension, methyl ester sulfonate, non-ionic, surfactantAbstrakKinerja metil ester sulfonat (MES) sebagai bahan chemical flooding untuk EOR telah dilakukan dengan menambahkan pengemulsi etil glikol mono butil eter (EGBE) dan etanol. MES memiliki nilai tegangan permukaan (IFT) sebesar 10-3 dyne/cm, tetapi memiliki kelarutan yang rendah dalam air formasi. Untuk memperbaiki sifat ini, MES ditambahkan dengannonyl phenol ethoxylate (Tergitol) sebagai surfaktan kedua, EGBE dan etanol. Hasil formulasi surfaktan diuji nilai IFT, kelarutan dan pengaruh termal terhadap nilai IFT dalam berbagai tingkat konsentrasi. Hasil pengujian mengindikasikan adanya pengaruh konsentrasi pengemulsi yang besar terhadap nilai IFT. Rantai karbon yang lebih panjang berakibat semakin mudah interaksi micelle terjadi. Kelarutan yang semakin tinggi disebabkan polaritas dari rantai panjang EGBE dan meningkatnya stabilitas mikroemulsi oleh alkohol. Hasil formulasi terbaik didapatkan pada konsentrasi surfaktan 1% dengan MES 40%, Tergitol 20%, Alkohol 40% dan konsentrasi surfaktan 0,3% dengan MES 40%, Tergitol 20%, EGBE 40%. Formula ini memiliki kelarutan yang lebih baik daripada MES karena hanya membentuk 1 fase. Pengaruh pemanasan 62,5 oC selama 1 hari menyebabkan IFT semakin rendah karena meningkatnya interaksi antara pengemulsi dan micelle. Pemanasan yang berlebihan menyebabkan IFT naik karena rusaknya struktur pengemulsi sehingga interaksi sulit terjadi.Kata kunci: EOR, metil ester sulfonat, non-ionik, surfaktan, tegangan permukaan